Competition and Bank Stability - Abel, Sanderson; Le Roux, Pierre; Mutandwa, Learnmore (International Journal of Economics and Financial Issues, 2018)
The study investigates the effect of competition on bank stability in the Zimbabwean banking sector. After encountering episodes of bank failures, which altered the competitive landscape and episodes of high non-performing loans which contributed to banking sector insolvency and bank failure motivated the study. The study uses a two - step method to establish whether the Zimbabwean banking systems adheres to competition stability or competition fragility hypothesis. In the first step the study estimates the measures of financial sector competition and stability. In the second step, the study applies the generalised method of moments dynamic panel data to test the “competition-stability” and “competition-fragility” hypothesis respectively. The results show that the banking sector supports the competition fragility hypothesis which means that an increase competition in the banking sector leads to banking fragility. Bank ownership has no influence on the stability of the banks. The study recommends that the central bank should closely monitor banks to ensure adherence to international best practice in credit management and moderate pro-competitive policies. Keywords: Competition, Stability, Fragility, Non-performing Loans, Lerner Index, Generalised Method of Moments JEL Classifications: G01, G21, G33